1993
DOI: 10.1104/pp.102.2.671
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and Photomorphogenic Nature of Ultraviolet-B-Induced Cotyledon Curling in Brassica napus L

Abstract: Three general classes of photomorphogenic photoreceptors have been characterized in higher plants: phytochrome, a blue lightl ultraviolet (UV)-A photoreceptor(s), and a UV-B sensory system(s). Although a great deal is known about phytochrome and the blue light/UV-A photoreceptor(s), little is known about UV-B detedion processes. One reason for this is the lack of readily quantifiable morphogenic responses that are specifically induced by UV-B radiation. We have discovered a response to UV-B, upward curling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 29 publications
6
41
0
1
Order By: Relevance
“…Fluence rates were adjusted by changing the distance of the lamps to the plants. To allow comparison with the work of others, we have estimated the biologically effective UV-B radiation as the cross-sectional overlap between the generalized plant action spectrum normalized to 300 nm (Caldwell et aL, 1986) and the spectral output of the Rayonet 300 nm photoreactor tube (Wilson and Greenberg, 1993a). For 0.25, 1 and 6 I~mol m -2 sec -1 of radiation in the UV-B region, the values were 0.11, 0.43 and 2.6 I~mol m -2 sec -1, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Fluence rates were adjusted by changing the distance of the lamps to the plants. To allow comparison with the work of others, we have estimated the biologically effective UV-B radiation as the cross-sectional overlap between the generalized plant action spectrum normalized to 300 nm (Caldwell et aL, 1986) and the spectral output of the Rayonet 300 nm photoreactor tube (Wilson and Greenberg, 1993a). For 0.25, 1 and 6 I~mol m -2 sec -1 of radiation in the UV-B region, the values were 0.11, 0.43 and 2.6 I~mol m -2 sec -1, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A greenhouse study of two species of Brassica (Feldheim and Conner 1996) found increases in female ®tness with increased UV-B in three of four cases, in spite of the fact that the family Brassicaceae is known to be sensitive to UV-B ( Van et al 1976;Hashimoto and Tajima 1980;Tevini et al 1981;Wilson and Greenberg 1993). However, responses of plants in the greenhouse to UV-B may be quite dierent from responses in the ®eld (Teramura 1986b;Teramura and Murali 1986).…”
Section: Introductionmentioning
confidence: 92%
“…Em Brassica napus L., o enrolamento está associado com a degradação da auxina na epiderme da face adaxial ou ainda, devido aos danos que a radiação causa às proteínas, ao DNA ou aos fotossistemas durante o desenvolvimento foliar (Wilson & Greenberg 1993;Krol et al 2000). O enrolamento das margens pode ser considerado como um mecanismo fotoprotetor das folhas para minimizar o efeito da radiação UV-B, uma vez que a área foliar exposta é menor.…”
unclassified